Characterization of Lung Inflammatory Response to Aspergillus fumigatus Spores - Alexandra Bouyssi; Tanguy Déméautis; Alexis Trecourt; Marie Delles; Fany Agostini; Guillaume Monneret; Olivier Glehen; Martine Wallon; Florence Persat; Gilles Devouassoux; Abderrazzak Bentaher; Jean Menotti (Journal of Fungi, 2023)
The airway exposure to Aspergillus fumigatus spores (AFsp) is associated with an inflammatory response, potentially leading to allergic and/or chronic pulmonary aspergillosis. The aim of our study is to better understand the host response, first in vitro, then in vivo, following the chronic exposure of mice to AFsp. We investigated the inflammatory response to AFsp in cell mono- and co-culture systems with murine macrophages and alveolar epithelial cells. The mice were subjected to two intranasal instillations using 105 AFsp. Their lungs were processed for inflammatory and histopathological analyses. In cell culture, the gene expressions significantly increased for TNF-α, CXCL-1, CXCL-2, IL-1β, IL-1α and GM-CSF in macrophages, with these increases being limited for TNF-α, CXCL-1 and IL-1α in epithelial cells. In co-culture, increases in the TNF-α, CXCL-2 and CXCL-1 gene expressions were observed to be associated with increased protein levels. The in vivo lung histological analyses of mice challenged by AFsp showed cellular infiltrates in the peribronchial and/or alveolar spaces. A Bio-Plex approach on the bronchoalveolar lavage revealed significant increases in the protein secretion of selected mediators of the challenged mice compared to the unchallenged mice. In conclusion, the exposure to AFsp resulted in a marked inflammatory response of macrophages and epithelial cells. These inflammatory findings were confirmed in mouse models associated with lung histologic changes.